2024
DOI: 10.1186/s12979-023-00395-z
|View full text |Cite
|
Sign up to set email alerts
|

The role of NLRP3 inflammasome in aging and age-related diseases

Ruikai Liang,
Xinrui Qi,
Qi Cai
et al.

Abstract: The gradual aging of the global population has led to a surge in age-related diseases, which seriously threaten human health. Researchers are dedicated to understanding and coping with the complexities of aging, constantly uncovering the substances and mechanism related to aging like chronic low-grade inflammation. The NOD-like receptor protein 3 (NLRP3), a key regulator of the innate immune response, recognizes molecular patterns associated with pathogens and injury, initiating an intrinsic inflammatory immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 113 publications
(108 reference statements)
0
2
0
Order By: Relevance
“…NLRP3 activation triggers the production of pro-inflammatory cytokines IL-1β and IL-18. This chronic inflammation contributes to diseases such as atherosclerosis, type 2 diabetes, and Alzheimer's disease ( 24 , 25 ). Among the various downstream pro-inflammatory pathways activated by the NLRP3 inflammasome, IL-1β and IL-18 emerge as potential contributors to inflammaging.…”
Section: Inflammaging and Cardiovascular Diseasesmentioning
confidence: 99%
“…NLRP3 activation triggers the production of pro-inflammatory cytokines IL-1β and IL-18. This chronic inflammation contributes to diseases such as atherosclerosis, type 2 diabetes, and Alzheimer's disease ( 24 , 25 ). Among the various downstream pro-inflammatory pathways activated by the NLRP3 inflammasome, IL-1β and IL-18 emerge as potential contributors to inflammaging.…”
Section: Inflammaging and Cardiovascular Diseasesmentioning
confidence: 99%
“…The intricate process of inflammation is strictly linked to the activation of NLRP3 inflammasomes (multiprotein complexes belonging to innate immunity), which, triggered by pathogen-and danger-associated molecular patterns via TLR4, leads to the production of IL-1β, thereby initiating a potent inflammatory response [8]. Robust evidence describes NLRP inflammasome dysfunction during aging and suggests that the activation and hyperactivation of NLRP3 inflammasomes strongly contribute to inflammaging and the onset and progression of age-related diseases [9]. To strengthen this evidence, in vivo studies showed that NLRP3 pathway inhibition mitigates age-related organ damage [10][11][12].…”
Section: Introductionmentioning
confidence: 99%